2014
DOI: 10.1002/ijc.28867
|View full text |Cite
|
Sign up to set email alerts
|

High coexpression of CCL2 and CX3CL1 is gender‐specifically associated with good prognosis in soft tissue sarcoma patients

Abstract: Chemokines are involved in both the negative and positive regulation of inflammatory processes, angiogenesis and cancer/cancer stem cell proliferation as well as the chemoattraction of tumor cells to metastatic sites. The aim of this study was to measure the mRNA expression levels of three chemokines, CCL2, CCL7 and CX3CL1, in soft tissue sarcomas (STSs) and to assess the correlations between these levels as well as their correlations with clinicopathological data and the disease-specific survival of STS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…Previous studies have shown that H level CX3CL1 in breast cancer, gastric cancer, and soft tissue sarcoma patients correlates with better prognosis . We found that higher levels of CX3CL1 correlate with poor prognosis only in AD/smoker group.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Previous studies have shown that H level CX3CL1 in breast cancer, gastric cancer, and soft tissue sarcoma patients correlates with better prognosis . We found that higher levels of CX3CL1 correlate with poor prognosis only in AD/smoker group.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies have shown that H level CX3CL1 in breast cancer, gastric cancer, and soft tissue sarcoma patients correlates with better prognosis. 11,12,21 We found that higher levels of CX3CL1 correlate with poor prognosis only in AD/smoker group. Most patients with SQ had smoking history, but patients with AD were either smokers or nonsmokers with a higher percentage of non-smokers.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, expression of the ligand has usually been associated with improved patient survival (26,44,53,54). The antitumor effects of CX 3 CL1 are mostly related to attraction of cytotoxic CD8 T lymphocytes and NK cells (40,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in resected pancreatic cancer patients, CCL2 is an independent favorable prognostic factor with indirect effects on pancreatic cancer cell growth via cytokines, such as IL1B [35]. Furthermore, in soft tissue sarcoma patients, high CCL2 mRNA expression is associated with a good prognosis [36], and higher CCL2 expression was significantly associated with better OS in non-small-cell lung cancer (NSCLC) patients [37]. In addition, a protective role of the CCR2/CCL2 chemokine pathway has been demonstrated by cytotoxic T lymphocytes' migration toward melanoma cells that secrete CCL2, which results in tumor cell apoptosis [38], and further by the recruitment of subsets of tumor-infiltrating lymphocytes (type 1 cytotoxic gamma-delta T lymphocytes) to tumor beds in a melanoma model [39].…”
Section: Introductionmentioning
confidence: 99%